Carbapenem-resistant Enterobacterales: Epidemiological study of isolates in a public hospital in Santa Fe (Actualizaciones en Sida e Infectología, 2023)
Introduction: The incidence of carbapenem-resistant Enterobacterales (CRE) rose in the last decade, and especially during the COVID-19 pandemic.Objective: To identify the antimicrobial resistance profile, as well as the frequency and type of carbapenems that were present in CRE isolations in a tertiary care hospital.Materials and methods: Epidemiological, observational and retrospective study. It included CRE isolated in clinical samples during 2021 in a tertiary care hospital in Argentina. Incidences (isolations/patients-day), confidence intervals of 95% (CI 95%) and statistical comparisons were made with OpenEpi.Results: 348 CRE were isolated (11.9 isolations/1,000 patients-day, IC95% 10.7-13.2). Incidence correlated to COVID-19 cases (rho=0.874, p
Keywords: Carbapenem-resistant Enterobacteriaceae; Carbapenems; Antibiotic resistance